Plasma-Derived Neuronal Exosomal CircRNAs as Potential Biomarkers for Central Nervous System Infections - Rui Zhang; Bihan Deng; Shuaibing Shi; Geng Lu; Jun Xia; Hongwei Liang; Fei Liu; Shuangshuang Gu; Jun Wang (Journal of Immunology Research)
Infections of central nervous system (ICNSs) are inflammatory diseases caused by infectious agents that can infiltrate the brain and spinal cord through various routes, including the bloodstream, peripheral nerves, or cranial nerves. Exosomes are found in plasma and have the capacity to cross the blood–brain barrier (BBB). Exosome constituents, including lipids, proteins, DNA, and RNA, change significantly over time and are correlated with the course of disease. Circular RNA (circRNA) has become a potential biomarker for various diseases, such as ICNSs. This study explores the diagnostic potential of circRNAs derived from brain-derived exosomes in ICNSs. Our research shows that the brain-derived exosomes from patients with CNS illnesses have different patterns of circRNA expression than those from healthy controls. Plasma samples from patients with bacterial ICNSs show significantly elevated levels of hsa_circ__0020840 and hsa_circ_0116108. In contrast, higher expression levels of hsa_circ_0056947 and hsa_circ_0021531 are observed in plasma samples from individuals with viral ICNSs compared to healthy subjects. These observations suggest their potential utility as sensitive and specific biomarkers for these diseases. Moreover, the capacity of circRNAs to be encapsulated within exosomes and released into circulation offers a noninvasive approach for diagnosing ICNSs. These findings highlight the promise of utilizing brain-derived exosomal circRNAs as novel diagnostic markers for ICNSs, which may have implications for improving patient outcomes and disease management.